2005
DOI: 10.1021/cm0508773
|View full text |Cite
|
Sign up to set email alerts
|

6Li NMR Studies of Cation Disorder and Transition Metal Ordering in Li[Ni1/3Mn1/3Co1/3]O2 Using Ultrafast Magic Angle Spinning

Abstract: Studies of Li[Ni 1/3 Mn 1/3 Co 1/3 ]O 2 prepared under six different conditions are compared using highresolution solid-state 6 Li NMR. Differing degrees of cation disorder are established via integration of the NMR resonances, and this quantification of cation disorder is compared with Rietveld refinements of powder X-ray and neutron diffraction studies. Chemical shift trends to high frequency with decreasing degrees of disorder are established among this family of samples and explained according to the orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 31 publications
12
107
0
Order By: Relevance
“…This ordering has been found to be the most favorable using solid state NMR. 30 This structure was also confirmed by DFT calculations of an initial set of 30 lowest energy configurations determined based on electrostatic interactions only (not shown). The ordering can be explained based on the local charge balance.…”
Section: Methodssupporting
confidence: 54%
“…This ordering has been found to be the most favorable using solid state NMR. 30 This structure was also confirmed by DFT calculations of an initial set of 30 lowest energy configurations determined based on electrostatic interactions only (not shown). The ordering can be explained based on the local charge balance.…”
Section: Methodssupporting
confidence: 54%
“…For an ideal LiMO 2 crystal, ionic configuration is regulated as Li at the 3a site (0,0,0), M at the 3b site (0,0, 1 = 2 ), and O at the 6c site (0,0, 1 = 4 ) [10]. According to previous experiments (i.e., X-ray absorption near edge structure, nuclear magnetic resonance, X-ray photoelectron spectroscopy), the oxidation states of Ni, Co, and Mn in the pristine material are proved to be +2, +3, and +4, respectively [11][12][13].…”
Section: Introductionmentioning
confidence: 85%
“…The shifts and the full width at half maximum of the resonances are reported in Table 5. According to the study reported by Cahill et al [36] the ratio of the smaller peak to that of the larger peak gives the degree of cation disorder. The values of the cation disorder 0.84% and 2.30% for ı = 0.025, and 0.075, respectively, are in good agreement with the values determined by Rietveld refinement of their X-ray powders diffraction patterns.…”
Section: Nmr Analysismentioning
confidence: 97%
“…The other decomposition bands are attributed to the various interactions Li O Ni and Li O Mn. Moreover, the set resonances at lower frequency correspond to the Li present in the Li oxide layers, while those at higher frequency are assigned to Li located in the transition metal layers [36]. The first set cannot be seen in the figure, because the first resonance is located at ca.…”
Section: Nmr Analysismentioning
confidence: 98%